2023
DOI: 10.1038/s41598-023-30626-8
|View full text |Cite
|
Sign up to set email alerts
|

A new Carboniferous edaphosaurid and the origin of herbivory in mammal forerunners

Abstract: Herbivory evolved independently in several tetrapod lineages during the Late Carboniferous and became more widespread throughout the Permian Period, eventually leading to the basic structure of modern terrestrial ecosystems. Here we report a new taxon of edaphosaurid synapsid based on two fossils recovered from the Moscovian-age cannel coal of Linton, Ohio, which we interpret as an omnivore–low-fibre herbivore. Melanedaphodon hovaneci gen. et sp. nov. provides the earliest record of an edaphosaurid to date and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The proliferation of FG feeding functionality among eothyridids, ophiacodontids, and sphenacodontians during the Kasimovian coincides with the first diversification of herbivorous tetrapods (Fig. 7 ) such as diadectids, captorhinids, and edaphosaurids 76 , 79 , 80 . These new prey possessed broad trunks and robust limbs 27 , making them a fleshier and so more calorific meal for predators, creating new selective pressures for terrestrial carnivores.…”
Section: Resultsmentioning
confidence: 91%
“…The proliferation of FG feeding functionality among eothyridids, ophiacodontids, and sphenacodontians during the Kasimovian coincides with the first diversification of herbivorous tetrapods (Fig. 7 ) such as diadectids, captorhinids, and edaphosaurids 76 , 79 , 80 . These new prey possessed broad trunks and robust limbs 27 , making them a fleshier and so more calorific meal for predators, creating new selective pressures for terrestrial carnivores.…”
Section: Resultsmentioning
confidence: 91%
“…On the rest of the picture, the extinct part, depend the answers to such questions as whether the origin of the amniote mode of reproduction involved a reduction in body size (Laurin, 2004, and references therein); when the first amniote lived, and when the last common ancestor of amniotes and lissamphibians lived (Pardo et al, 2020;Marjanović, 2021); what those ancestors' morphology and ecology were (e.g. Buchwitz et al, 2021); which ecological guilds formed by amniotes today were formed by sauropsids, stem-pan-mammals, stem-pan-amniotes or stem-amphibians in which periods and geographic areas, and how the diversity of these taxa changed over time (Mann et al, 2021a(Mann et al, ,b, 2022a(Mann et al, , 2023aBrocklehurst, 2021); and which of the similarities between extant amniotes and extant lissamphibians are inherited and which are convergent-in other words, what the lissamphibians that are commonly used as model organisms can and cannot really tell us about ourselves. Phylogenetics using paleontological data is important even for biomedical research.…”
Section: ↑ Figure 1 (A)mentioning
confidence: 99%
“…To these I have added:  the very well known caseid caseasaur Martensius (Berman et al, 2020);  the sphenacodont material currently called "Haptodus garnettensis", in order to sample secure pan-mammals (although these specimens probably do not belong to Haptodus, and may not be monophyletic with respect to other sphenacodontians, which are, however, not sampled here) (Laurin, 1993;Spindler, 2015);  the edaphosaurid pan-mammal Ianthasaurus (Reisz & Berman, 1986;Modesto & Reisz, 1990;Mazierski & Reisz, 2010;Mann et al, 2023a);  the ophiacodontid pan-mammals Ophiacodon (Williston and Case, 1913;Romer and Price, 1940) and Varanosaurus (Watson, 1914;Romer and Price, 1940;Sumida, 1989;Berman et al, 1995), which are quite different from each other (including Archaeothyris, the likely sistergroup to all other ophiacodontids, is currently impractical);  the varanopids Ascendonanus (Spindler et al, 2018) and a composite of Mesenosaurus romeri, M. efremovi and Cabarzia (Reisz & Berman, 2001;Spindler et al, 2019;Maho et al, 2019) to better represent Varanopidae -note that M. efremovi is exclusively known from skulls, so it cannot be compared directly to Cabarzia, known only from a head-and neckless articulated skeleton, meaning that its genus assignment (Maho et al, 2019) is arbitrary;  Thuringothyris, thought to be the sister-group of Captorhinidae Müller and Reisz, 2006);  Euconcordia, the oldest captorhinid (Müller and Reisz, 2005;Reisz et al, 2016), to further break up the long branch of Captorhinus (Müller and Reisz, 2006);  Opisthodontosaurus, a captorhinid that is very similar in some respects to the gymnarthrid microsaur Euryodus (Reisz et al, 2015) and has played an important role in connecting captorhinids and microsaurs in Pardo et al (2017) through Pardo ( 2023);  Brouffia, a Paleothyris-grade animal reported (Carroll and Baird, 1972) to have dorsal dermal scales -a plesiomorphy widely retained in microsaurs (and adult lysorophians: J. Pardo, pers. comm.…”
Section: Added and Removed Taxa Presumably Relevant To Amniote Origin...mentioning
confidence: 99%